A Self‐Sustaining Antioxidant Strategy for Effective Treatment of Myocardial Infarction. Issue 5 (25th December 2022) - Sun, Quan; Ma, Hongqin; Zhang, Jiaxiong; You, Baiyang; Gong, Xiaohui; Zhou, Xiaolin; Chen, Jin; Zhang, Guogang; Huang, Jia; Huang, Qiong; Yang, Yurong; Ai, Kelong; et al.
Abstract: Myocardial infarction (MI) is the leading cause of death worldwide and can lead to the loss of cardiac function and heart failure. Reactive oxygen species (ROS) play a key role in the pathological progression of MI. The levels and effects of ROS are significantly different in three unique pathological stages of MI, and most antioxidants cannot make corresponding adjustments to eliminate ROS, which leads to a great compromise to treat MI with antioxidants. Herein, an innovative self‐sustaining antioxidant strategy is developed to treat MI with self‐sustaining selenium‐embedded nanoparticles (SSSe NPs). SSSe NPs possess unique self‐sustaining antioxidant effects at different pathological stages of MI. This strategy of on‐demand ROS elimination during different pathological stages demonstrated excellent MI treatment efficacy and effectively reversed heart failure to normal heart function. The therapeutic mechanism of SSSe NPs is intensively investigated through a series of experiments and mainly involved five critical aspects of myocardial repair: protecting mitochondria, reducing cardiomyocyte apoptosis and ferroptosis, reducing inflammation and fibrosis, and promoting angiogenesis. This strategy not only provides a promising treatment option for MI but also offers inspiration for other ischemic diseases. Abstract : An innovative self‐sustaining antioxidant strategy to treat MI through self‐sustaining selenium‐embedded nanoparticles (SSSe NPs). SSSe NPs possess unique self‐sustaining antioxidant effects at different pathological stages of MI. SSSe NPs could repair the injured myocardium by protecting mitochondria, reducing cardiomyocyte apoptosis and ferroptosis, reducing inflammation and fibrosis, and promoting angiogenesis.